A Randomized, Placebo-controlled Laboratory Study of the Effects of D-cycloserine on Craving in Cocaine-dependent Individuals - Price, Kimber L. (2012)
RATIONALE: D-cycloserine (DCS), a partial glutamate NMDA receptor agonist, enhances extinction of conditioned fear responding; preliminary data suggests that it may facilitate extinction of drug cue reactivity. OBJECTIVE: This study investigates DCS effects on cocaine cue craving and drug use in cocaine-dependent subjects. METHODS: Thirty-two subjects were randomly assigned to receive 1) DCS only, 2) DCS before sessions 1 and 3, PBO before session 2 or 3) PBO only 15-min before each of 3 1-hour cocaine cue exposure sessions conducted 1 day apart. Craving ratings were obtained before, during and after sessions. Drug use and cue-induced craving were assessed 1 week after the last cue session. RESULTS: Repeated presentation of cocaine cues resulted in decreased craving both within and between sessions. DCS did not facilitate extinction learning and may have enhanced craving. The group that received 3 doses of DCS had significantly higher craving than the PBO group at the baseline ratings taken before sessions 2 and 3, as well as significantly higher cue-induced craving at follow-up. The group that received 2 doses of DCS did not differ from the PBO group. There were no group differences in post-extinction cocaine use. CONCLUSIONS: The reduction of cocaine cue reactivity in the PBO group suggests that the study procedures were sufficient to produce extinction. Under these conditions, DCS did not facilitate extinction and may have enhanced craving. Further studies of glutamatergic agents and extinction in cocaine dependence should include consideration of procedural variables that could have a major impact on study outcomes.